2017
DOI: 10.1186/s13019-017-0623-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Staphylococcus aureus on Outcomes after Valvular Surgery for Infective Endocarditis

Abstract: BackgroundAs Staphylococcus aureus (SA) remains one of the leading cause of infective endocarditis (IE), this study evaluates whether S. aureus is associated with more severe infections or worsened outcomes compared to non-S. aureus (NSA) organisms.MethodsAll patients undergoing valve surgery for bacterial IE between 1995 and 2013 at our institution were included in this study (n = 323). Clinical data were retrospectively collected from the chart review. Patients were stratified according to the causative orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 12 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Streptococcus species were protective from mortality when compared with a negative culture. Though not statistically significant in the model, Staphylococcus aureus , the next most commonly isolated species has been associated with a more severe clinical presentation and worse long‐term survival in prior literature 10,11 . Our patients with IVDU more commonly had MRSA and MSSA positive cultures.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Streptococcus species were protective from mortality when compared with a negative culture. Though not statistically significant in the model, Staphylococcus aureus , the next most commonly isolated species has been associated with a more severe clinical presentation and worse long‐term survival in prior literature 10,11 . Our patients with IVDU more commonly had MRSA and MSSA positive cultures.…”
Section: Discussionmentioning
confidence: 57%
“…Outcomes for patients undergoing surgery for infective endocarditis, with and without a history of IVDU; for each readmission type, the total number of readmissions for all patients, the mean number of readmissions per patient (with standard deviation), and the median time to the first readmission for each patient (with interquartile range, in years) are shown Streptococcus species were protective from mortality when compared with a negative culture. Though not statistically significant in the model, Staphylococcus aureus, the next most commonly isolated species has been associated with a more severe clinical presentation and worse long-term survival in prior literature 10,11. Our patients with IVDU more commonly had MRSA and MSSA positive cultures.…”
mentioning
confidence: 51%
“…Staphylococcus aureus infection was correlated with death in univariate cox regression analysis in our study and also in EURO ENDO registry [ 9 ]. Staphylococcus aureus patients have more severe IE compared to non- Staphylococcus aureus patients, with higher rates of preoperative vascular complications, septic shock, embolic events, stroke, and annular abscess [ 42 ]. Staphylococcus aureus IE is associated with more severe prognosis than other pathogens (excluding fungal pathogens), with a high in-hospital mortality of 30% to 46%, according to various authors [ 10 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, several studies have found that Staphylococcus aureus infection is associated with higher mortality rates in a variety of infectious diseases [40,41,42,43]. The higher rate of Staphylococcus aureus infection in diabetic patients conveys an important message, that is, this infection is associated with higher rates of both complications and mortality in IE, and these findings have been confirmed by several studies [42,43,44,45]. Third, the ratio of receiving surgical intervention is lower in the with DM group compared to the without DM group in our study.…”
Section: Discussionmentioning
confidence: 99%